LITERASI VISUAL SEBAGAI PENANGKAL FOTO HOAX COVID-19 - Widiatmojo, Radityo (JURNAL SOSIAL POLITIK, 2020)
The spread of hoax on health issue is a compelling phenomenon in digital era. By focusing on visual literacy as a way to avoid hoax, this qualitative research attempts to find how visual hoax operated. The main concept of Visual Literacy proposed by Maria Avgerinou, reading the spectrum of an image by Roland Barthes and six dimension of photograph life by Widiatmojo are used to analysis visual hoax. The result shows that visual hoax on corona virus occurred as the time frame dimension were diminished, the meaning was changed as well as the narration of the original image, the topic was compromised, the lost of image quality and the distribution on social media by anonymous identity. Therefore, people need to have basic competence in visual literacy, which is the ability to understand visual language accompanied by the ability to think and analyze. It will make an individual produce a positive perception that should be use to avoid hoaxes.